2003
DOI: 10.1051/0004-6361:20030894
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the solar chromosphere IV. Evidence for atmospheric gravity waves from TRACE

Abstract: Abstract. We study the low-frequency brightness modulation of internetwork regions in the low solar chromosphere using simultaneous ultraviolet and white-light image sequences from the Transition Region and Coronal Explorer (TRACE). The ultraviolet sequences exhibit a slowly varying brightness pattern in internetwork regions on which the more familiar acoustic three-minute oscillation is superimposed, with about half of the peak brightness reached in internetwork grains contributed by the low-frequency backgro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 19 publications
5
41
2
Order By: Relevance
“…Studies of the H I Lyman continuum (Wilhelm and Kalkofen 2003) and the C II 133.5 nm multiplet (Judge et al 2003) both indicated a heating of the upper chromosphere by magnetic effects and not by acoustic waves. However, Gallagher et al (1999) found indications of heating by acoustic shocks even in the transition region near 2.5 × 10 5 K. Evidence for atmospheric gravity waves was found from TRACE observations (Rutten and Krijger 2003).…”
Section: Chromospheric Oscillationsmentioning
confidence: 97%
“…Studies of the H I Lyman continuum (Wilhelm and Kalkofen 2003) and the C II 133.5 nm multiplet (Judge et al 2003) both indicated a heating of the upper chromosphere by magnetic effects and not by acoustic waves. However, Gallagher et al (1999) found indications of heating by acoustic shocks even in the transition region near 2.5 × 10 5 K. Evidence for atmospheric gravity waves was found from TRACE observations (Rutten and Krijger 2003).…”
Section: Chromospheric Oscillationsmentioning
confidence: 97%
“…In the evanescent regime (7 min oscillations), most of the internetwork exhibits small absolute phase differences (between ±20 degrees), as is expected for standing or evanescent waves. Larger negative phase differences have been attributed to downward propagating gravity waves (Cauzzi et al 2000;Krijger et al 2001;Rutten & Krijger 2003).…”
Section: Phase Differences and Coherencementioning
confidence: 99%
“…According to the VAL-C solar atmosphere model (Vernazza et al 1981), the temperature minimum region is located at about 500 km above τ 500 = 1, corresponding to the upper photosphere/lower chromosphere (Worden et al 1999;Rutten & Krijger 2003;McAteer et al 2004).…”
Section: Formation Height Of Emission From Trace Uv Filtersmentioning
confidence: 99%